Abrasive treatment of microtiter plates improves the reproducibility of bacterial biofilm assays. Issue 57 (19th September 2018) - Bordeleau, Emily; Mazinani, Sina Atrin; Nguyen, David; Betancourt, Frank; Yan, Hongbin
Abstract : The reproducibility of bacterial biofilm assays is improved using abrasively-treated microtiter plates. Abstract : Microtiter plate-based bacterial biofilm assay is frequently used to study bacterial biofilm development and growth. While this assay is simple and relatively high-throughput, it frequently shows difficulty in establishing robust biofilm attachment in the wells. We report that the consistency of bacterial biofilm assays carried out in microtiter plates subjected to abrasive treatment, by sandblasting or drill press grinding, is significantly improved in a Pseudomonas fluorescens Pf0-1 model. Scanning electron microscopy imaging suggests that the treated surfaces could provide points of attachment to facilitate the recruitment of bacteria in the initial phase of biofilm colony establishment. The sandblast treated polypropylene, but not polystyrene, plates were found suitable in studying the impact of flavonoid quercetin on the biofilm formation in Bacillus subtilis FB17. Further investigation revealed that due to the hydrophobicity of the polystyrene surfaces, a greater amount of quercetin was adsorbed on the plate surface, effectively lowering the concentration of the flavonoid in solution.